Artificial Intelligence in Hydrology 2024
DOI: 10.2166/nh.2022.044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the long short-term memory (LSTM) network for discharge prediction under changing climate conditions

Abstract: Better understanding the predictive capabilities of hydrological models under contrasting climate conditions will enable more robust decision-making. Here, we tested the ability of the long short-term memory (LSTM) for daily discharge prediction under changing conditions using six snow-influenced catchments in Switzerland. We benchmarked the LSTM using the HBV bucket-type model with two parameterizations. We compared the model performance under changing conditions against constant conditions and tested the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…For instance, if the current measured water quality is worse than the historical records, a ML model is likely to perform worse than a physical model. There is evidence that this claim might also hold true for the modern and more sophisticated data-driven models (de Moura et al 2022 ). However, large-sample hydrology (LSH), which is aimed at understanding hydrological processes at multiple spatiotemporal scales and under changing conditions (Addor et al 2020 ) is somewhat challenging this regime.…”
Section: Different Modeling Approachesmentioning
confidence: 91%
“…For instance, if the current measured water quality is worse than the historical records, a ML model is likely to perform worse than a physical model. There is evidence that this claim might also hold true for the modern and more sophisticated data-driven models (de Moura et al 2022 ). However, large-sample hydrology (LSH), which is aimed at understanding hydrological processes at multiple spatiotemporal scales and under changing conditions (Addor et al 2020 ) is somewhat challenging this regime.…”
Section: Different Modeling Approachesmentioning
confidence: 91%
“…The LSTM is a type of neural network that allows the autocorrelation often seen in hydrological variables to be modelled. It is commonly used in hydrology for simulation, forecasting, and hydroclimate predictions (e.g., Kratzert et al, 2018;Le et al, 2019;Natel de Moura et al, 2022) Perceptron Artificial Neural Network to forecast short-term irrigation water demand. They found that, although the forecasts had a skill comparable to previous studies, the lack of inclusion of physical understanding of the system limited the performance of the method.…”
Section: Data-driven and Hybrid Methodsmentioning
confidence: 99%
“…The primary focus of the studies cited above was so far on model training and validation on a future part of the time series or on catchments not used for calibration. The question whether this success is transferable to the prediction of the consequences of modified driving forces in these catchments is less certain (Bai et al, 2021;Natel de Moura et al, 2022). For the prediction of the effects of climate change and water management measures on the hydrology of catchments, it is of particular interest to modify driving forces beyond the patterns observed in the past.…”
Section: Introductionmentioning
confidence: 99%